HUBUNGAN MOTIVASI KERJA DENGAN DISIPLIN KERJA APARAT KODIM 1401 MAJENE - Samsul Bahri; Aco Dahrul (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2019)
This study aims to analyze the relationship between work motivation and work discipline officials. Using primary data obtained using a questionnaire. Sampling was done using the convenience sampling method. The sample in this study amounted to 15. The analysis used is a simple correlation. The results showed that motivation and work discipline had a significant relationship with employee performance. The results of the correlation found that work motivation is the most dominant correlation variable for the work discipline tool greater than 0.482 or the 45.3% correlation with the work motivation variable whose value is below the work discipline variable.